Possible improvement in uteroplacental blood flow during atrial natriuretic peptide infusion in preeclampsia - Grunewald, C; Nisell, H; Jansson, T; Kublickas, M; Thornström, S; Nylund, L (Obstetrics and gynecology (New York. 1953), 1994)
To study the effects of low doses of the hormone atrial natriuretic peptide (ANP) on uteroplacental blood flow in patients with preeclampsia. Eleven women with preeclampsia were infused intravenously with ANP (10 ng/kg/minute). Uteroplacental blood flow index was measured using dynamic placental scintigraphy with indium-113m. Regional blood flows were assessed by pulsed Doppler ultrasound and expressed as pulsatility index (PI). Hemodynamic measurements and blood sampling for peripheral venous plasma analysis of cyclic guanosine monophosphate (cGMP), an ANP second messenger, were performed before and after 30 minutes of infusion. Nonparametric statistics were used. The uteroplacental blood flow index increased by 28% (-2 to 58%; mean and 95% confidence interval). The Doppler findings were unaffected. Mean arterial blood pressure decreased from 112 (108-117) to 108 (103-114) mmHg (P < .01). Cyclic GMP increased significantly from 9.2 (6.2-12.3) to 17.4 (12.3-22.6) nmol/L (P < .01). Subjects exhibiting a substantial increase in uteroplacental blood flow index (25% or more) demonstrated a significantly greater cGMP response (P < .01) than those who did not (6% or less increase). A tendency to an increased uteroplacental blood flow index combined with minor blood pressure reduction after ANP infusion suggest the possibility of uteroplacental vasodilatation.